Identifying Areas of High Gold Potential Using Geochemical Prospecting Methods: The Tenado area in the Boromo Birimian Belt, West-Central Burkina Faso, West Africa - Fayçal Tarnagda; Pascal Ouiya; Sâga Sawadogo (European Scientific Journal, ESJ, 2023)
The investigation area is located in the central-western region of Burkina Faso, in a geological environment that incorporates the Paleoproterozoic formations of the Boromo greenstone belt. The area already hosts several gold showings and an active zinc mine, but no major gold deposits. The aim of this study is to define target areas with high gold potential for further prospecting. To meet this objective, we used mainly geochemical methods.The combination of gold content in stream sediments and litho-geochemical data has enabled us to highlight two areas of gold (Au) and various metal anomalies. Gold content in stream sediments is mainly influenced by that of the source rock from which it is derived. Indeed. high gold anomalies are found in clay sediments more than in sand sediments. Clay sediments are derived from basic rocks (basalt) and intermediate rocks (andesite-dacite). whereas gold-poor sandy sediments are derived from granitoids. Basic to intermediate rocks are fertile for primary gold. Anomaly zone one (01) in the northern part of the study area (Kelsio, Zoula, Poa and Dyoro) and anomaly zone two (02) in the southern part of the study area (Kwademan. Baguiomo, Bérédo, Bonga and Baganapou) show occurrences of mainly gold and various metals (Zn. Cu. Ni).